Quantitative molecular viral loads in 7 horses with naturally occurring equine herpesvirus‐1 infection. (30th December 2014) - Estell, K. E.; Dawson, D. R.; Magdesian, K. G.; Swain, E.; Laing, S. T.; Siso, S.; Mapes, S.; Pusterla, N.
Summary Reasons for performing study Data associating quantitative viral load with severity, clinical signs and survival in equine herpesvirus‐1 myeloencephalopathy (EHM) have not been reported. Objectives To report the clinical signs, treatment, and temporal progression of viral loads in 7 horses with naturally occurring EHM and to examine the association of these factors with survival. Study design Retrospective case series. Methods The population included 7 horses with EHM presented to the University of California, Davis William R. Pritchard Veterinary Medical Teaching Hospital from May to September 2011. Horses were graded using a neurological grading scale. Daily quantitative PCR was performed on nasal secretions and whole blood. Treatment, survival, outcome and histopathology were reported. Results At presentation, one horse was neurological grade 5/5, 3 were grade 4/5 and 3 were grade 3/5. All were treated with anti‐inflammatory drugs, valacyclovir and management in a sling if necessary. All were infected with equine herpesvirus‐1 of DNA polymerase D752 genotype. Peak viral load in nasal secretions and blood of 5 survivors ranged from 6.9 × 103 to 2.81 × 105 (median 5.11 × 104) and from 143 to 4340 gB gene copies/million eukaryotic cells (median 3146), respectively. The 2 nonsurvivors presented with grade 3/5 neurological signs and progressed to encephalopathy. Peak viral load was higher in nonsurvivors, with levels in nasal secretions of 1.9 × 109 and 2.2 × 109 and in blood of 2.05 × 104 and 1.02 × 105gB gene copies/million eukaryotic cells. Case fatality was 2/7. Conclusions Nonsurvivors had viral loads 1000‐fold higher in nasal secretions and 10‐fold higher in blood than survivors. There was no relationship between severity of clinical signs at presentation and survival. Thus, encephalopathy and high viral load were negatively associated with survival in this population. Further research should be performed to determine whether high viral loads are associated with encephalopathy and poor prognosis. The Summary is available in Chinese – see Supporting information.